Synthesis of tetraethyl pyrophosphate (TEPP): from physician Abbot and pharmacist Riegel to chemist Nylen - Petroianu, Georg (Die Pharmazie, 2015)
Tetraethyl pyrophosphate (TEPP) made history not only as the first man-made organophosphate cholinesterase inhibitor but also as a most successful commercial product traded under a good number of names. The substance was first synthesized by a Russian chemist, Wladimir Petrovich Moshnin, while studying in Paris as an eleve (student) of Wurtz. The synthesis was soon thereafter repeated and reported to the Academy of Sciences by Philippe de Clermont, another student of Wurtz, who acknowledged the earlier work of Moshnin. Holmstedt in his chapter dealing with the beginnings of organophosphate chemistry in Koelle's Textbook Cholinesterases and Anticholinesterase Agents concluded his remarks by noting that after the initial synthesis by Moshnin and de Clermont, over the years, a good half-a-dozen of other pharmacists and chemists also managed the feat (of synthesizing TEPP). This led to my attempts at identifying those involved in the synthesis of TEPP. The compiled list turned out to be quite long: Abbot (1879), Riegel (1896), Cavalier (1906), Rosenheim A, Stadler & Jacobsohn (1906), Rosenheim & Pritze (1908), Balareff (1914), Nylen (1930), Arbusow & Arbusow (1931), Schrader (1938), Woodstock (1946) and Toy (1948). This report while summarizing the synthetic approach used in obtaining TEPP by the respective scientists mainly attempts to shed light on the life of the less known pharmacists and chemists involved in the synthesis of TEPP. The focus is on the pre-industrial synthesis period ending with Nylen largely because details on the Arbusow family, as well as on Schrader and Toy are fairly well known or have recently been described.
Gesehen am 13.12.2018